(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Interlocking compressed earth bricks (ICEB) are a cleaner and sustainable alternative to conventional fired bricks and it has comparable strength to other masonry systems, making it feasible for both cladding and load-bearing purposes. However, it tends to be brittle and has poor performance under impact loading. Impact resistance of masonry walls are important as one of the main purposes of cladding is to protect its occupants from external projectiles. This study was commissioned to investigate the feasibility incorporating both crumb rubber (CR) and treated CR into ICEBs in place of sand to improve its impact resistance. The drop weight impact tests carried out concluded that ICEBs containing CR have better impact resistance and this was further improved with heat-treated CR. Heat-treated CR ICEBs also had less catastrophic failure compared to untreated CRs which had pieces of materials spalling off. Mechanical tests also show that this improvement in impact resistance comes at the expense of a minor loss in compressive and flexural strength at replacement levels higher than 7.5 %. Heat-treated CRs also showed higher losses of mechanical strength compared to untreated CRs.